Family History of Diabetes and the Effectiveness of Lifestyle Intervention on Insulin Secretion and Insulin Resistance in Chinese Individuals with Metabolic Syndrome. (5th January 2021) - Zhu, Haiqing; Chen, Xiaoping; Zhang, Bo; Yang, Wenying; Xing, Xiaoyan
Abstract : Aims . The current study aims to explore if a family history of diabetes can influence the efficiency of lifestyle intervention on insulin secretion and study the insulin resistance in Chinese men and women with metabolic syndrome in a cohort with a 2-year follow-up. Methods . 151 individuals (90 individuals did not have a family history of diabetes (DMFH (-)) and 61 with a family history of diabetes (DMFH (+)) with metabolic syndrome participated in the lifestyle intervention program at baseline and finished with 1-year follow-up. 124 individuals have two-year follow-up data. A family history of diabetes was ascertained by self-report. Lifestyle interventions were individual sessions on lifestyle changes. Results . During the 1-year follow-up, Ln Insulinogenic index (Δ baseline − 1 year = 0.29 ± 0.65, P = 0.001 ) and 30-min glucose (Δ baseline − 1 year = − 0.41 ± 1.71, P = 0.024 ) changed significantly in the DMFH(-) group; in the DMFH(+) group, Ln ISIm (Δ baseline − 1 year = − 0.22 ± 0.60, P = 0.022 ) and 30-min glucose (Δ baseline − 1 year = 0.53 ± 1.89, P = 0.032 ) changed significantly, and there was no significant change of other parameters. The change of 30 min glucose during a 1-year intervention has shown a significant difference between the two groups (P = 0.002 ). During the 2 years intervention, Ln Insulinogenic index changed significantly in the DMFH(-) group (Δ baseline − 1 year = 0.33 ± 0.66, P < 0.001 and Δ baseline − 2 year = 0.43 ± 1.17, P = 0.034 ). Fasting insulin (Δ baseline − 2 year = 2.95 ± 8.69, P = 0.034 ), 2 h insulin (Δ baseline − 2 year = 23.75 ± 44.89, P = 0.002 ), Ln HOMA-B (Δ baseline − 2 year = 0.43 ± 1.02, P = 0.009 ), Ln HOMA-IR (Δ baseline − 2 year = 0.53 ± 1.04, P = 0.002 ), Ln ISIm (Δ baseline − 2 year = 0.52 ± 0.95, P = 0.004 ), and Ln Insulinogenic index (Δ baseline − 2 year = 0.66 ± 1.18, P = 0.047 ) changed significantly after 2 years of intervention, compared to the baseline in the DMFH(+) group. The change of Ln ISIm (P = 0.023 ), fasting (P = 0.030 ), and 2 h insulin (P = 0.007 ) during the 2-year intervention has shown a significant difference between the two groups. Family history of diabetes was related with a 0.500 unit increase in 2-year ISIm (P = 0.020 ) modified by lifestyle intervention adjusted for age, baseline BMI, sex, and baseline waist circumference and a 0.476 unit increase in 2-year ISIm (P = 0.027 ) with extra adjustment for weight change. Conclusions . Patients with a family history of diabetes benefit more from lifestyle intervention in regard to insulin resistance than those without a family history of diabetes adjusting for age, baseline BMI, sex, baseline waist circumference, and weight change.